2016
DOI: 10.1074/jbc.m115.706200
|View full text |Cite
|
Sign up to set email alerts
|

The Methionine Transamination Pathway Controls Hepatic Glucose Metabolism through Regulation of the GCN5 Acetyltransferase and the PGC-1α Transcriptional Coactivator

Abstract: Methionine is an essential sulfur amino acid that is engaged in key cellular functions such as protein synthesis and is a precursor for critical metabolites involved in maintaining cellular homeostasis. In mammals, in response to nutrient conditions, the liver plays a significant role in regulating methionine concentrations by altering its flux through the transmethylation, transsulfuration, and transamination metabolic pathways. A comprehensive understanding of how hepatic methionine metabolism intersects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Intriguingly, recent studies have shown that GCN5 is an important regulator of cell metabolism. In addition to being activated by its coenzyme acetyl-CoA, the acetyltransferase activity of GCN5 can also be up-regulated by the essential amino acid methionine and insulin-GSK3b signals [27][28][29]. In addition to being activated by its coenzyme acetyl-CoA, the acetyltransferase activity of GCN5 can also be up-regulated by the essential amino acid methionine and insulin-GSK3b signals [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, recent studies have shown that GCN5 is an important regulator of cell metabolism. In addition to being activated by its coenzyme acetyl-CoA, the acetyltransferase activity of GCN5 can also be up-regulated by the essential amino acid methionine and insulin-GSK3b signals [27][28][29]. In addition to being activated by its coenzyme acetyl-CoA, the acetyltransferase activity of GCN5 can also be up-regulated by the essential amino acid methionine and insulin-GSK3b signals [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these enzymes involved in the Met cycle are Met adenosyltransferase (1A MAT1a), and phosphatidylethanolamine methyltransferase (PEMT). Supplementation with RPC in cows has demonstrated that hepatic gene expression associated with antioxidant synthesis and DNA methylation status were improved (Osorio et al, 2014) and studies with liver hepatocytes from rodents show the relationship among the Met and hepatic glucose synthesis through PGC-1α (Tavares et al, 2016). The relationship between gluconeogenic factors and methylation affected by nutrition levels (Rattanatray et al, 2014) deserves more attention in ruminant studies.…”
Section: Fermentation Gas Parametersmentioning
confidence: 99%
“…Phosphatidylcholine participates in the synthesis and export of triglycerides in very low density lipoproteins (Zeisel, 2006) and this has affected plasma NEFA and cholesterol (Pinotti et al, 2003). Choline has increased liver glycogen (Piepenbrink & Overton, 2003) and Met transamination pathways promote the activation of the transcriptional coactivator PGC-1α, which is involved in the control of hepatic gluconeogenesis (Tavares et al, 2016); PGC-1α plays a central role in the regulation of cellular energy metabolism, (Liang & Ward, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Tris-HCl buffer (pH 7.4) served as a blank. All results were normalized to respective protein content [58]. …”
Section: Methodsmentioning
confidence: 99%
“…NAD+ concentrations were determined fluorometrically in dilutions of the supernatant sample using alcohol dehydrogenase (Sigma-Aldrich, St. Louis, MO). Excitation was at 339 nm, and emission wavelength was at 460 nm in a spectrofluorimeter (Spectra MaxGeminiXS, Sunnyvale, CA) [58]. …”
Section: Methodsmentioning
confidence: 99%